Plant-derived Molecules for the Treatment of Tuberculosis: A Review - Yadav, Meena; Sharma, Poonam (Iraqi Journal of Pharmaceutical Sciences, 2022)
Synthetic anti-TB drugs are being used to treat tuberculosis (TB) as they are effective, however, they are accompanied by many side effects. The disease has remained largely uncured till date. The use of plant extracts or phytochemicals along with the anti-TB drugs is a very attractive strategy to make the treatment more effective as phytochemicals have no side-effects, are much less toxic than synthetic anti-TB drugs, are safe to use and most importantly, do not produce resistant strains as opposed to synthetic anti-TB drugs. Approximately 420,000 plant species have been identified globally and among them only a few have been explored for their therapeutic potential. Traditional medicine in different parts of the world has employed crude extracts of several plant species to cure tuberculosis. Several anti-TB phytochemicals have been found in plants that are identified to have therapeutic qualities. These phytochemicals are majorly glycosides, flavonoids, triterpenes, phenolic compounds, alkaloids, flavonoids, diterpenoid, lipids, tannins, sterols etc. by nature. They are either antimycobacterial or act synergistically with anti-TB drugs and reduce their adverse effects. Phytochemicals ameliorate the symptoms either by reducing the oxidative stress in the afflicted tissues or by regulating the inflammatory response. Hence, plant derived molecules have great potential to be used for the alternative treatment strategy for TB in future.